2013
DOI: 10.1007/978-3-642-40477-1_5
|View full text |Cite
|
Sign up to set email alerts
|

Nudging People Away from Privacy-Invasive Mobile Apps through Visual Framing

Abstract: Abstract. Smartphone users visit application marketplaces (or app stores) to search and install applications. However, these app stores are not free from privacy-invasive apps, which collect personal information without sufficient disclosure or people's consent. To nudge people away from privacy-invasive apps, we created a visual representation of the mobile app's privacy rating. Inspired by "Framing Effects," we designed semantically equivalent visuals that are framed in either a positive or negative way. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 25 publications
2
65
1
Order By: Relevance
“…Privacy nudges entail people having a choice between two fairly equivalent options and the nudge persuades them to choose the wiser option (Choe et al, 2013;Jeske et al, 2014). Nudging in authentication does not match this pattern of use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Privacy nudges entail people having a choice between two fairly equivalent options and the nudge persuades them to choose the wiser option (Choe et al, 2013;Jeske et al, 2014). Nudging in authentication does not match this pattern of use.…”
Section: Discussionmentioning
confidence: 99%
“…One study (Choe et al, 2013) used positive visual framing to direct people away from privacy-invasive apps on smartphones. Balebako et al (2011) made the case for moving away from a hurdle to a paternalistic approach (i.e.…”
Section: Related Workmentioning
confidence: 99%
“…Wilson et al studied the effect of predetermined privacy profiles to assist users with location sharing disclosures [30]. Choe et al investigated the impact of the "framing" heuristic (i.e., people would prefer alternatives that are framed as gains over those framed as loses, even when the two alternatives are equivalent) in the context of mobile apps selection; and found that the framing effect had minimal impact on participants' trust perceptions [10]. A recent longitudinal Facebook study highlighted how profoundly Facebook interface changes can impact users' information sharingindicating a potential for Facebook privacy nudges [23].…”
Section: Soft-paternalism and Privacy Nudgesmentioning
confidence: 99%
“…A lot of private and often sensitive information about users that is collected through ubiquitous devices can be shared with unknown entities at any time, without them being aware. In order to control which of their personal data is being collected, who can collect such data, and when this is allowed, users currently need to go through and pre-set privacy rules for devices/applications they want to use [2,11,12]. Even then, controlling the diffusion of such information has become an increasingly daunting task, especially due to the innumerable possibilities of information flow and varying privacy preferences of users across different contexts.…”
Section: Introductionmentioning
confidence: 99%